Expressions of microaggressions against women in the healthcare context: a critical incident approach - Piccinelli, E. (2020)
Purpose. Patients belonging to social minorities can be exposed to various forms of discrimination in the healthcare context. Previous research in this domain has overlooked expressions of microaggressions against women and the role of intersectional identities. This study aims to uncover the themes that underly the experience of microaggressions by diverse women in Portugal. Methods. Using an interview model based on the Critical Incident Technique (Flanagan, 1954) 17 women were interviewed about their microaggression experiences in the healthcare setting. Among those with an intersectional identity, social minority membership was also based on ethnicity, LGB sexual orientation and functional diversity. Results. A total of 17 microaggressive themes were retrieved, five of which were found to be related to microaggressions towards women in general and a total of seven were unique for women with specific intersectional identities. Another four themes reflected providers’ general attitudes towards patients without being related to gender or any intersectional minority group, and one theme described systemic microaggressions. Conclusion. Some of the retrieved themes reflect microaggressions that women seem to experience in their everyday life but that are exacerbated by the health provider-patient power disparity. Some themes appear to be specific to the healthcare context and related to providers’ lack of patient-centeredness.